World/Space/Place in Service for Civil Society Mobilization: Ukrainian Case - Dzyadevych, Tetiana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences)
This paper focuses on the political language symbolism used during the political protests in Ukraine (in 1990, 2000-2001, 2004, 2013-14). Firstly, author discusses the strategies used by the slogan writes during the political protests and shows that they were aimed at mobilizing civil consensus. Secondly, author is interested in the evolution of the language produced during the ongoing protest in Ukraine, and how it delineates the space for the expression of political agenda.